Evaluation of adherence of patients with atrial fibrillation to anticoagulant therapy at the outpatient stage of treatment - A. V. Sokolov; T. E. Lipatova; O. V. Reshetko (Izdatelstvo OKI, 2021)
Despite clinical guidelines for the treatment of atrial fibrillation (AF) patient adherence to oral anticoagulants (OACs) in routine clinical practice remains low. Assessing the factors affecting adherence to the OACs regimen and developing strategies for its improvement is important. Aim. To assess the adherence of patients with AF to the prescribed anticoagulant therapy at the outpatient stage of treatment. Methodology. The object of the study was 165 patients with nonvalvular AF undergoing treatment in a specialized cardiology department or receiving outpatient treatment in a specialized cardiological dispensary in Saratov from February 2018 to December 2019. After 3, 6, 12 months, a telephone contact with the patients was carried out, a specially designed questionnaire was filled out, in which the anticoagulant therapy received by AF patients was reflected, the Morisky-Green questionnaire was filled out, the answers of patients about the reasons for skipping or stopping the administration of the OACs were recorded. Results. After 3 months. 16.6 % of AF patients replaced the OACs intake with antiplatelet agents, 16 % refused antithrombotic therapy; 43.1 % of AF patients were adherent to OACs. After 6 months. antiplatelet agents were taken by 24.5 % patients (p<0.05), 11.9 % completely stopped taking antithrombotic drugs; 30.8 % of patients were adherent to OACs (p<0.05). After 12 29,5 % patients replaced OACs treatment with antiplatelet agents, 7.6 % patients did not take any antithrombotic drugs; 31.8 % of AF patients were adherent to OACs. The most common reasons for a decrease in the adherence to OACs therapy were the cost of drugs, lack of understanding of the value of OACs administration in AF, and the lack of appreciable effect of OACs administration. Conclusion. At the outpatient stage of treatment, there was an insufficient level of adherence of AFpatients to OACs treatment.